Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/srep11107
|View full text |Cite|
|
Sign up to set email alerts
|

DW-F5: A novel formulation against malignant melanoma from Wrightia tinctoria

Abstract: Wrightia tinctoria is a constituent of several ayurvedic preparations against skin disorders including psoriasis and herpes, though not yet has been explored for anticancer potential. Herein, for the first time, we report the significant anticancer properties of a semi-purified fraction, DW-F5, from the dichloromethane extract of W. tinctoria leaves against malignant melanoma. DW-F5 exhibited anti-melanoma activities, preventing metastasis and angiogenesis in NOD-SCID mice, while being non-toxic in vivo. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 37 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…Nuclear extracts of the cells treated with or without the compound were prepared and EMSA was conducted to evaluate DNA-binding activity of NF-κ B as described earlier2729 (SI methods).…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear extracts of the cells treated with or without the compound were prepared and EMSA was conducted to evaluate DNA-binding activity of NF-κ B as described earlier2729 (SI methods).…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear accumulation of β-catenin, a key regulator of Wnt path way is found to be important in melanoma progression ( Widlund et al, 2002 ; Chien et al, 2009 ). A recent report from our lab has shown that a fraction, DW-F5 isolated from Wrightia tinctoria inhibits the proliferation and progression of melanoma tumor by down-regulating the pivotal molecules such as Brn-2, β-catenin and BRAF along with MITF-M, the master regulator of melanocyte development ( Antony et al, 2015 ). It was very interesting to note that DETS also strongly down-regulate the expression of β-catenin revealing the efficacy of this compound in regulating Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The viability of cells upon treatment with heteronemin and/or cytarabine was determined by MTT assay as described earlier [ 42 ] and the relative cell viability percentage is expressed as (Abs 570 of treated wells/Abs 570 of untreated wells) × 100.…”
Section: Methodsmentioning
confidence: 99%